2021
DOI: 10.3390/antiox10030446
|View full text |Cite
|
Sign up to set email alerts
|

Redox Active Antimicrobial Peptides in Controlling Growth of Microorganisms at Body Barriers

Abstract: Epithelia in the skin, gut and other environmentally exposed organs display a variety of mechanisms to control microbial communities and limit potential pathogenic microbial invasion. Naturally occurring antimicrobial proteins/peptides and their synthetic derivatives (here collectively referred to as AMPs) reinforce the antimicrobial barrier function of epithelial cells. Understanding how these AMPs are functionally regulated may be important for new therapeutic approaches to combat microbial infections. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…The antimicrobial activities of endogenous AMPs include inactivation of pathogenic microbes, reinforcing the antimicrobial barrier function of epithelial cells particularly in the gut, and linking innate immunity to adaptive immunity ( 76 , 77 ). The cationic nature of endogenous AMPs facilitate their ability to exert antimicrobial effect(s) on pathogens.…”
Section: Mitigating Microbial Resistance To Endogenous Antimicrobial Peptides In Food Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial activities of endogenous AMPs include inactivation of pathogenic microbes, reinforcing the antimicrobial barrier function of epithelial cells particularly in the gut, and linking innate immunity to adaptive immunity ( 76 , 77 ). The cationic nature of endogenous AMPs facilitate their ability to exert antimicrobial effect(s) on pathogens.…”
Section: Mitigating Microbial Resistance To Endogenous Antimicrobial Peptides In Food Animalsmentioning
confidence: 99%
“…Furthermore, the presence of thioredoxin, a redox protein present at the intestinal epithelial surface, is known to facilitate the antimicrobial activity of AMPs ( 86 ). A recent report by has also suggested that redox active AMPs can undergo reversible oxidation after interaction with some electron transport chain proteins and their products, or interaction with the periplasmic redox system of Gram-negative bacteria ( 77 ). Further research is required to identify molecular-based strategies that will exploit the reversible oxidation state of endogenous AMPs, for the synthesis of AMPs that will have improved stability in the gut mucosa and other epithelial membranes.…”
Section: Mitigating Microbial Resistance To Endogenous Antimicrobial Peptides In Food Animalsmentioning
confidence: 99%
“…Chemerin, which was originally identified as a chemoattractant protein for antigen-presenting cells [ 4 ], is currently recognized to have antimicrobial properties [ 5 ]. This protein has an inhibitory effect on commensal pathogen activity, including Escherichia coli and Staphylococcus aureus which are the major mastitis-causing pathogens [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, secretion of reducing and oxidizing factors can regulate the activity of cysteine-containing AMPs that form disulfide bonds essential for their folding and activity [16][17][18][19][20][21][22][23][24][25][26][27][28] . For instance, pro-inflammatory processes involve oxidative stress through elevating reactive oxygen species (ROS) concentrations [23][24][25]29 . In parallel, some pathogens can promote and express reducing factors that diffuse the oxidativedependent processes of inflammation and affect the activity of cysteine-rich AMPs 25,26,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, in the presence of elevated concentrations of a reduction agent, the antibiotic activity of the human b-defensin 3, which is a cysteine-rich AMP, decreased, while that of bdefensin 1 increased, indicating distinct structure-function relationships and physiological regulation of antimicrobial peptides via reductive pathways 28,29,31,32 .…”
Section: Introductionmentioning
confidence: 99%